CHARACTERIZATION OF GEOTHERMAL POTENTIAL USING 2D MAGNETOTELLURIC INVERSION AT TELAGA TUJUH WARNA, LEBONG REGENCY, BENGKULU PROVINCE, INDONESIA - Maesaroh, Rina Maesaroh; Farid, Muchammad; Refrizon, Refrizon; Sumajaya, Erlan; Al Ansory, Andre Rahmat; Naldo, Asrol (Universitas Mataram, 2025)
The Telaga Tujuh Warna area in Lebong Regency exhibits geothermal manifestations such as hot water, mud craters, and fumaroles. This research aims to characterize the geothermal potential using 2D Magnetotelluric (MT) inversion. Measurements were conducted with the ADU-07e Magnetotelluric device, involving a 16-hour measurement period. Data collection followed the sounding principle with three frequency levels: high (4096 Hz), medium (1024 Hz), and low (128 Hz), spaced approximately 500 meters apart. Analysis confirms the consistency between 1D and 2D resistivity models, generating a resistivity distribution cross-section. Key findings include: (1) a low-resistivity cap layer (20–40 Ω-m) at approximately 1 km depth; (2) a medium-resistivity reservoir (40–160 Ω-m) at depths of 1–2 km; (3) a high-resistivity geothermal resource (>300 Ω-m) at depths of 1–2.5 km; and (4) a zone with very low resistivity values (2–16 Ω-m) at depths less than 1 km, potentially indicating a fumarole emitting hot water vapor and gas through rock fractures. These findings aim to advance geothermal exploration in Lebong Regency and support Indonesia's renewable energy objectives.